2012
DOI: 10.1177/147470491201000304
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Relationship Regret: The Role of Perceived Mate Characteristics

Abstract: Abstract:The current set of studies examined regret involving action and inaction in the realm of romantic relationships by testing whether such regret is associated with the characteristics of one's mate. In study 1, 394 participants reported on a previous casual sexual encounter, and in study 2, 358 participants reported on a previous romantic relationship. In both, instances of actual engagement and instances of passing up opportunities were studied. Study 3 was experimental and elicited reactions to hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…In the face of an extensive literature that has highlighted a significant difference in the frequency and quality of the experience of regret between genders ( Roese et al, 2009 ; Coats et al, 2012 ; Newton et al, 2012 ; Galperin et al, 2013 ), the test of invariance in measurement with DRS reassures the reliability of assessing regret in both genders. The gender study of measurement invariance showed crucial features connected to probable gender disparities in a person’s Regret experience.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of an extensive literature that has highlighted a significant difference in the frequency and quality of the experience of regret between genders ( Roese et al, 2009 ; Coats et al, 2012 ; Newton et al, 2012 ; Galperin et al, 2013 ), the test of invariance in measurement with DRS reassures the reliability of assessing regret in both genders. The gender study of measurement invariance showed crucial features connected to probable gender disparities in a person’s Regret experience.…”
Section: Discussionmentioning
confidence: 99%
“…Women appear to be especially prone to feeling regret after hooking up. Even though regret is the most common negative response to hooking up for both men and women (e.g., Coats, Harrington, Beaubouef, & Locke, 2012; Eshbaugh & Gute, 2008; Fisher, Worth, Garcia, & Meredith, 2012; Galperin et al, 2013; Oswalt, Cameron, & Koob, 2005), numerous studies suggest that women are more likely than men to regret their hookup (Fisher et al, 2012; Garcia et al, 2012). For these reasons, we focused this study on women’s emotional reactions to hookups and the motivational predictors that might help disentangle these responses.…”
Section: Emotional Responses To Hooking Upmentioning
confidence: 99%